2011
DOI: 10.1089/ast.2011.0660
|View full text |Cite
|
Sign up to set email alerts
|

An Extensive Phase Space for the Potential Martian Biosphere

Abstract: We present a comprehensive model of martian pressure-temperature (P-T) phase space and compare it with that of Earth. Martian P-T conditions compatible with liquid water extend to a depth of *310 km. We use our phase space model of Mars and of terrestrial life to estimate the depths and extent of the water on Mars that is habitable for terrestrial life. We find an extensive overlap between inhabited terrestrial phase space and martian phase space. The lower martian surface temperatures and shallower martian ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 145 publications
(153 reference statements)
0
33
0
1
Order By: Relevance
“…Microbial metabolism is revealed at temperatures at least down to −33 • C [88,89]. Moreover, it is shown that econiches with liquid water and positive temperatures can occur on the current Mars [88,[90][91][92][93]. Terrestrial microorganisms can grow under combined low pressure, temperature, and anoxic atmosphere conditions [94], it can withstand the impact of Martian salts and strong oxidizers [95][96][97][98], and can survive in subzero brines [99,100].…”
Section: Implications For Habitability Assessmentmentioning
confidence: 99%
“…Microbial metabolism is revealed at temperatures at least down to −33 • C [88,89]. Moreover, it is shown that econiches with liquid water and positive temperatures can occur on the current Mars [88,[90][91][92][93]. Terrestrial microorganisms can grow under combined low pressure, temperature, and anoxic atmosphere conditions [94], it can withstand the impact of Martian salts and strong oxidizers [95][96][97][98], and can survive in subzero brines [99,100].…”
Section: Implications For Habitability Assessmentmentioning
confidence: 99%
“…The decrease in Mars' deep geothermal gradient would have caused the gradual downwards migration of the base of the frozen crust. Even if the average surface temperatures on early Mars were still sub-zero (Kite et al, 2014;Squyres and Kasting, 1994), it is plausible that under an ancient geothermal gradient (e.g., >15 K/ km, from a heat flow of >30 mW/m 2 and a thermal conductivity of <2 W/m/K for crustal rocks, Jones et al, 2011), melting temperatures for pure water ice could be reached within the top 1 km of the subsurface. Hence it is likely that some ancient low latitude craters may have excavated through the cryosphere, and thus been influenced by a very different volatile stratigraphy than later craters which impacted during a lower martian heat flow.…”
Section: Evolution Of Volatiles Through Timementioning
confidence: 99%
“…Despite many indicators of the role of volatiles in the emplacement of layered ejecta and morphological similarities with those produced by laboratory and numerical simulation experiments involving water ice (e.g., Baloga et al, 2005), there is as yet only indirect evidence that water ice or liquid water was necessarily involved in their formation. Understanding the potential connections between layered ejecta craters and subsurface volatiles is, therefore, of high importance, particularly given the astrobiological implications of locating subsurface water ice below the seasonal melting isotherm (Jones et al, 2011). If some subset of the diverse population of layered ejecta craters are tracers of subsurface water, they could be utilised to identify environments that may be have been hospitable in the martian past, or may still be hospitable if volatiles persist at depth (Cockell, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The planet Mars is considered a promising astrobiological exploration target owing to its relative proximity and similarity to Earth, coupled with increasing evidence pointing to the past and present existence of liquid water at the surface and near subsurface (2)(3)(4). The current surface environment of Mars presents formidable challenges to life, such as a scarcity of liquid water and organic nutrients, extreme low temperatures, a low-pressure CO 2 -dominated atmosphere, harsh solar and galactic cosmic radiation, and a lack of organic nutrients (5).…”
Section: Astrobiology | Planetary Protectionmentioning
confidence: 99%